Single-layered organic photovoltaics with double cascading charge transport pathways: 18% efficiencies - Ming Zhang (Nature Portfolio, 2021)
Efficiency of organic solar cells is determined by the physical properties of donors and acceptors in bulk heterojunction film. The authors optimise quaternary blends to realize a double cascading energy level alignment enabling efficient carrier dissociation and transport, achieving 18% efficiency.